Retracted: The Effect of Peripheral Neuromodulation on Pain from the Sacroiliac Joint: A Retrospective Cohort Study. Issue 7 (13th April 2017) - Goroszeniuk, Teodor; Shetty, Ashish; Munglani, Rajesh; Hegarty, Dominic; Bhaskar, Arun
Abstract : The above article, first published online on 13 April 2017 in Wiley Online Library (www.onlinelibrary.wiley.com ) has been retracted by agreement between the authors, the Editor‐in‐Chief, E.A. Joosten, and Wiley Periodicals, Inc. The retraction has been agreed at the request of the authors, who advised that it has been brought to their attention that some of the long‐term outcome data set may no longer be easily and independently verifiable. The Editor‐in‐Chief, therefore, has made the decision to retract the article based on the information as specified in the authors' request attributable to honest error on behalf of the authors. References: 1Goroszeniuk T, Shetty A, Munglani R, Hegarty D, Bhaskar A .The Effect of Peripheral Neuromodulation on Pain from the Sacroiliac Joint: A Retrospective Cohort Study .Pain Pract . 2017.https://doi.org/10.1111/papr.12567 .